Geological tourist mapping of the Mount Serrone fault Geosite (Gioia dei Marsi, Central Apennines, Italy). Issue 2 (3rd July 2019) - Piacentini, Tommaso; Miccadei, Enrico; Berardini, Gianclemente; Aratari, Luigi; De Ioris, Antonio; Calista, Monia; Carabella, Cristiano; d'Arielli, Roberto; Mancinelli, Vania; Paglia, Giorgio; Buccolini, Marcello
ABSTRACT: The Geological tourist map of the Mount Serrone fault Geosite (Gioia dei Marsi, Italy) has been realized for describing, in an educational perspective, the surface expression of one of the main active faults of the Central Apennines, connected with the 1915 Fucino earthquake (magnitude 7, historically, one of the strongest in Italy). The Central Apennines are a mountain range whose landscape is deeply connected to active tectonics and seismicity, as documented by recent earthquakes. In this framework, the map is a useful tool for the dissemination of the geological knowledge of the Fucino area and faults in general and for the promotion of a geological landscape through a modern, sustainable and environmentally aware tourism. The map is double-sided with simple texts and cartoons on the front outlining general info about the geosite, faults and earthquakes, how to behave in seismic areas and historical notes. The back shows the Main Map with its visual legend featuring the main geological and tectonic elements of the Mount Serrone fault Geosite and the long term history of the landscape. Through simple keywords and concepts, tectonics, faults and earthquakes are shown to be natural features that have contributed to shape the landscape of the Apennines over geological time, as well as something to be afraid and worried of, as they are connected to natural hazard and disasters. This approach is aimed at increasing people's awareness of geological processes and hazards (i.e. seismic), which with adequate knowledge and proper land management, can be lived with.